2019
DOI: 10.7554/elife.49915
|View full text |Cite
|
Sign up to set email alerts
|

Kv1.1 contributes to a rapid homeostatic plasticity of intrinsic excitability in CA1 pyramidal neurons in vivo

Abstract: In area CA1 of the hippocampus, the selection of place cells to represent a new environment is biased towards neurons with higher excitability. However, different environments are represented by orthogonal cell ensembles, suggesting that regulatory mechanisms exist. Activity-dependent plasticity of intrinsic excitability, as observed in vitro, is an attractive candidate. Here, using whole-cell patch-clamp recordings of CA1 pyramidal neurons in anesthetized rats, we have examined how inducing theta-bursts of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…Data were obtained from male Wistar rats between the ages of postnatal day 25 (P25) to P35 (weight range, 90–110 g). Recordings were made as previously described (Morgan et al., 2019 ). On the day of the recordings, the animals were anesthetized (induction: 3% isoflurane; maintenance: Xylazine/Ketamine 10/100 mg/Kg, supplemented with ketamine 20 mg/Kg).…”
Section: Methodsmentioning
confidence: 99%
“…Data were obtained from male Wistar rats between the ages of postnatal day 25 (P25) to P35 (weight range, 90–110 g). Recordings were made as previously described (Morgan et al., 2019 ). On the day of the recordings, the animals were anesthetized (induction: 3% isoflurane; maintenance: Xylazine/Ketamine 10/100 mg/Kg, supplemented with ketamine 20 mg/Kg).…”
Section: Methodsmentioning
confidence: 99%
“…Showing cognitive deficits and gene expression rescue, the data pointed towards the latter. Importantly, Kv1.1 has been recently associated with in vivo homeostatic response, where to compensate network hyperexcitability, neurons increased endogenous Kv1.1 expression leading to a clear reduction of their firing rate (Morgan et al, 2019 ). These data together provide new insights, but also open a new series of questions, on the possible homeostatic mechanisms occurring in chronic established epilepsy.…”
Section: Therapeutic Interventions Based On the “Genetic Lead” Of Hommentioning
confidence: 99%
“…It indicates that the brain is in a chronic altered state in which homeostatic plasticity cannot maintain activity in its physiological boundaries, but that with a “homeostatic boost” in the direction of a reduction in neuronal excitability, the entire network may be able to rearrange itself to a less excitable state and take back control of phase-space regulation. Because Kv1.1 is implicated in fast homeostatic response in vivo , its increase could potentially drive the network compensation observed (Morgan et al, 2019 ). Indeed, the potential homeostatic role of Kv1.1 expression has been also corroborated in other experimental settings.…”
Section: Therapeutic Interventions Based On the “Genetic Lead” Of Hommentioning
confidence: 99%
“…Thus, they indicated that postsynaptic neuronal excitability gated presynaptic inputs and proposed a unique cellular mechanism for the generation of place codes. These studies have been followed by investigations on intracellular mechanisms for spatial representation in the rodent limbic system, including the hippocampus [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ] and the medial entorhinal cortex [ 110 , 111 ].…”
Section: In Vivo Whole-cell Recordings From Awake Animalsmentioning
confidence: 99%